Analisis kandungan klorofil pada daun suji dan daun pandan menggunakan spektrofotometer-vis sebagai alternatif pewarna alami - Sofia, Isna Anisatun (Maliki Interdisciplinary Journal, 2024)
The use of natural food colorings is one of the efforts to support food security in Indonesia in accordance with the Republic of Indonesia Law Number 18 of 2012 concerning Food. One of the most common examples of natural food coloring is chlorophyll obtained from suji and pandan leaves. Therefore, this experiment was conducted to determine the chlorophyll content in suji and pandan leaves using methanol and acetone extraction solutions. In this experiment, chlorophyll present in suji and pandan leaves was extracted with the help of methanol and acetone solvents, and then the chlorophyll content was analyzed using a Vis spectrophotometer. The research results showed that the highest chlorophyll content was obtained in the pandan leaf extract using acetone solvent, with a chlorophyll a value of 19.118 mg/l and chlorophyll b value of 54.436 mg/l. The total chlorophyll content in the pandan leaf extract reached 73.274 mg/l. Meanwhile, the suji leaf extract using methanol solvent resulted in the lowest chlorophyll content, with a chlorophyll a value of 0.295 mg/l and chlorophyll b value of 0.127 mg/l. The total chlorophyll content in the suji leaf extract was only 0.425 mg/l.